Motivation for Process of Land Use Changes and Urban Expansion in an Area in Vietnam - Quang Hien Truong; Van Tuyen Dinh (My University, 2017)
Motivation for Process of Land Use Changes and Urban Expansion in an Area in Vietnam
Keywords: Biến động sử dụng đất; Mở rộng đô thị; Động lực thay đổi